2001
DOI: 10.1177/026553220101800301
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Yes/No vocabulary test: some methodological issues in theory and practice

Abstract: This article evaluates the characteristics of the Yes/No test as a measure for receptive vocabulary size in second language (L2). This evaluation was conducted both on theoretical grounds as well as on the basis of a large corpus of data collected with French learners of Dutch. The study focuses on the internal qualities of the format in comparison with other more classical test formats. The central issue of determining a meaningful test score is addressed by providing a theoretical framework distinguishing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 14 publications
0
56
2
1
Order By: Relevance
“…The mean difference was statistically significant, t(175) ¼ 2.38, p ¼ .018, r ¼ .593. The false alarm rate is high when compared to previous research, where it ranged from 5% (Mochida & Harrington, 2006;Harrington & Carey, 2009) to 20% (Beeckmans, Eyckmans, Janssens, Dufranne, & Van de Velde, 2001;Cameron, 2002).…”
Section: Test Performancecontrasting
confidence: 68%
“…The mean difference was statistically significant, t(175) ¼ 2.38, p ¼ .018, r ¼ .593. The false alarm rate is high when compared to previous research, where it ranged from 5% (Mochida & Harrington, 2006;Harrington & Carey, 2009) to 20% (Beeckmans, Eyckmans, Janssens, Dufranne, & Van de Velde, 2001;Cameron, 2002).…”
Section: Test Performancecontrasting
confidence: 68%
“…Despite the fact that vocabulary studies have observed that learners tend to be conservative in their judgments about whether they know words and underestimate rather than overestimate their knowledge (Meara), it is possible that learners are not as conservative in their estimate of familiarity for expressions. In fact, studies by Eyckmans, Van de Velde, and colleagues suggest that learners significantly overestimate their knowledge on yes/no tests even for vocabulary items (Beeckmans, Eyckmans, Janssens, Dufranne, & Van de Velde, 2001;Eyckmans, Van de Velde, Van Hout, & Boers, 2007), so the finding for expressions may not be unusual. In addition, the use of a written format for conversational expressions might have led to an exaggeration of self-reported recognition.…”
Section: Previous Interlanguage Pragmatics Research On Conventional Ementioning
confidence: 99%
“…Clearly, the trustworthiness of learners' self-evaluations is debatable (Ross, 1998), so that these results may not be sufficient to cast doubt on the applicability of Dialang vocabulary test as a quick evaluation of learners' level in the four skills, but the limited applicability of vocabulary tests has already been pointed out by other researchers (cf. Beeckmans et al, 2001). More specifically, Eyckmans (2004) reported the failure of Dialang vocabulary test to account for the effects of cognates, something that may clearly play a relevant role for Italian learners of L2 French.…”
Section: Final Discussionmentioning
confidence: 99%